Dynamic Behavior of Materials, Volume 1 Proceedings of the 2013 Annual Conference on Experimental and Applied Mechanics - Song, Bo.; Casem, Dan.; Kimberley, Jamie; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This critical collection examines a range of the dynamic behavior of materials, from low-impedance materials to geo-materials to fracture and failure, as presented in early findings and case studies from the Proceedings of the 2013 Annual Conference on Experimental and Applied Mechanics. The collection includes papers in the following general technical research areas: • General Dynamic Material Properties • Novel Dynamic Testing Techniques • Dynamic Fracture and Failure • Novel Testing Techniques • Dynamic Behavior of Geo-materials • Dynamic Behavior of Biological and Biomimetic Materials • Dynamic Behavior of Composites and Multifunctional Materials • Dynamic Behavior of Low-Impedance materials • Multi-scale Modeling of Dynamic Behavior of Materials • Quantitative Visualization of Dynamic Behavior of Materials • Shock/Blast Loading of Materials Dynamic Behavior of Materials: Proceedings of the 2013 Annual Conference on Experimental and Applied Mechanics is the first volume of eight from the Conference.
From the Contents: Dynamic Deformation Behavior of AA2099-T8 Under Compression and Torsion Loads -- High Strain Rate Performance of Pressureless Sintered Boron Carbide -- Interpretation of Strain Rate Effect of Metals -- High Strain Rate Friction Response Of Porcine Molar Teeth And Temporary Braces -- Dynamics of Interfaces with Static Initial Loading -- Loading Rate Effects on Mode I Delamination of Z-pinned Composite Laminates -- Multi-scale Testing Techniques for Carbon Nanotube Augmented Kevlar -- Single Fiber Tensile Properties Measured by the Kolsky bar Using the Direct Fiber Clamping Method -- A Testing Technique for Characterizing Composite at Strain Rates up to 100/s.
Keywords: Nanotechnology; Mechanics; Mechanics, Applied; Nanotechnology and Microengineering; Theoretical and Applied Mechanics; Nanotechnology